Numerical simulation of MHD Sakiadis flows of convectively heated thixotropic nanofluids in a porous medium using revised transport laws and Wakif-Buongiorno's model - A. Wakif (Partial Differential Equations in Applied Mathematics, 2025)
Due to the particular inability of Fourier's and Fick's laws in the realistic quantification of transfer processes that can occur certainly within a flowing biphasic mixture, on the one hand, and the explanation of the memory relaxation features of such a non-homogenous medium, on the other hand, the present scrutinization intends to propose a representative biphasic flow model to reveal the principal demeanors of convectively heated thixotropic nanofluids during their steady two-dimensional flows in the laminar regime over a stretching planar geometry in a Darcy-Forchheimer porous medium under the magnetic impact of an external electromagnetic device. For this purpose, the renovated formulation of Wakif-Buongiorno's model is linked theoretically with the constructive equation of the thixotropic model and the generalized transport laws to describe properly the nanofluid motion, the thermal energy balance, and the nanoparticles’ molar concentration distribution under the assumptions of the boundary layer concept and the passive nanoparticles’ control approach. After numerous simplifications and feasible linearizations, the leading dimensionless system is solved numerically by applying an accurate collocation approach. As the main outcomes, it is noted that the upper thixotropic parameters speed up remarkably the thixotropic nanofluid motion and diminish its temperature locally, whilst reverse dynamical and thermal trends are witnessed for the bigger porosity and magnetic parameters. Further, it is remarked also that the increasing and decreasing changes in the thermal and concentration relaxation parameters don't affect the thixotropic nanofluidic medium dynamically. On the contrary, the rising thermal and concentration relaxation parameters lead to dissimilar thermal impressions, in which a cooling effect is produced within the thixotropic nanofluidic medium when elevating the thermal relaxation parameter, while a slight heating behavior is witnessed for the superior concentration relaxation parameters.